Corporate Social Responsibility Dalam Value Perusahaan Dengan Profitabilitas Dan Ukuran Perusahaan Sebagai Variabel Moderating - Taufiq, Muuchamad (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2019)
This study aims to determine whether the Corporate Social Responsibility affect the value of the company to profitability and the size of the company as variable moderang. This study is based on the theory that the rise and fall in value is influenced by the reporting company's Corporate Social Responsibility towards the public and variable proritabilitas well as the size of company that is considered capable of affecting the value of the company as Corporate Social Responsibility reporting to company value decreases and increases. This research is a quantitative research in the form of hypothesis testing. The method used in this research is descriptive statistical methods, this study uses an external data source with secondary data obtained from the financial statements issued by companies listed on the Indonesian Stock Exchange (BEI),. The test in doing this research is the analysis of test data and test hypotheses and test the significance of studies using multiple linear regression. The results showed Corporate Social Responsibility positive effect on firm value with significance 0.012. Profitability as a moderating variable 1 does affect the Corporate Social Responsibility and the value of the company the significance value of 0.048. The size of the company as a moderating variable 2 is considered a positive influence on Corporate Social Responsibility and the value of the company with a significance value of 0.049. This research is consistent with prior research as explained in the discussion.